A COMPARATIVE STUDY OF THE QUALITY OF EDUCATION IN PUBLIC ELEMENTARY SCHOOLS AND PUBLIC MADRASAH IBTIDAIYAH: A PARENT'S PERSPECTIVE - Husein, Dahyar (JURNAL TARBIYAH, 2025)
This study aims to compare the quality of education between Public Elementary Schools (SDN) and Public Islamic Elementary Schools (MIN) in Medan City based on parents' perspectives. Educational quality is understood as a multidimensional concept encompassing academic and non-academic aspects, such as teacher competence, facilities, academic achievement, character education, religious education, social skills, and the school environment. This study used a mixed methods approach with a sequential explanatory design, beginning with the collection and analysis of quantitative data through a Likert-scale questionnaire with 20 parents of grades IV–VI (10 parents from SDN and 10 parents from MIN), followed by semi-structured interviews to deepen understanding of the quantitative findings. Quantitative data analysis was conducted using comparative tests (t-test and ANOVA), while qualitative data were analyzed thematically. The results showed that there were no significant differences between SDN and MIN in terms of academic quality, including teacher competence, learning methods, and student readiness to continue to the next level of education. However, there were significant differences in the aspect of facilities, where SDN was considered superior. In contrast, MIN (Min) demonstrated significant excellence in non-academic aspects, particularly character education, religious education, social skills, and the school's social environment. These findings indicate that SDN (State Elementary School) and MIN (Min) each have their own strengths that influence parents' preferences in choosing a school. This study concludes that the quality of primary education in Medan City is determined not only by academic achievement but also by character formation and a supportive social environment, and provides important implications for developing more holistic and equitable education policies.